Growing Poverty - Deprivation Problems and Limits of Social Rights - Koray, Meryem (ISTANBUL UNIV, 2010)
The relation between poverty or distribution injustice and human rights is dimensional, but either the acceptance of this relation or the human rights, especailly socio-economic rights, themselves are problematic. Therefore we meet highly debateful area where various ideas and discussions come into being. In this article I tried to give, to some extend, some ideas about these debates and approaches as well as some problems in these discussions. For instance, in spite of huge discussions there are severe limitations of these debates on this extended and not well-defined problem. The considerable limitation is that most of the discussions do not refer the poverty to the current economic system and policies. Yes, meeting with the phenomenon like the increasing the poverty as well as the richness gives way the dicovering of the poverty again, especially by the international organizations; however it is preferred not to see it as the problem of the globalized capitalism, or the neo-liberal policies. With this approach, human aid becomes the essential remedy. Even for them who look at the problem as the violation of human rights, the main matter turns to the increasing of the international aids. In brief, I tried to emphasize in this article that the global poverty must be understood as the global economic injustice mainly caused by the dominant economic system and while the dominant understanding is far from coming to this point it is worty of remark to discuss the problem in this framework.
Keywords: Poverty; Neoliberal Polic ies; Globalized Capitalism; Social Rights; Human Aid; Government & Law